Paciente masculino de 69 años de edad con hipertensión arterial, obesidad grado 1 y evento cerebrovascular. - Moreno Mejía, Galo Enrique (2020)
The present clinical case is about a 69-year-old patient who resides in Babahoyo, was diagnosed with arterial hypertension 10 years ago and a cerebrovascular event 2 years ago, in the family history his mother died of arterial hypertension and his father of diabetes, the nutritional assessment is carried out in which it refers a body mass index of 32.35 kg/m2 which is interpreted as obesity grade I; In addition, laboratory tests were performed in which he presented low levels of HDL and high levels of HDL, cholesterol, and triglycerides, which are interpreted respectively as hypercholesterolemia and Hypertriglyceridemia, this due to his diet high in saturated fat and simple carbohydrates in addition to her caregiver did not provide her with enough vegetables and fruits, the physical examination revealed difficulty walking due to her cerebrovascular event and excess weight. A food plan is made according to the nutritional needs of the patient, which consists of a low sodium diet of 2.5 to 4 g per day of sodium, low in saturated fat which will be divided into 5 meals a day, that is, three main meals and two snacks at times appropriate for the patient, this meal plan will be based on the most frequent intake of vegetables and fruits. Through follow-up and monitoring, improvements are observed in the patient, his biochemical tests improved notably, decreasing cholesterol, LDL and triglyceride values, and increasing HDL values.